A Supramolecular Ice Growth Inhibitor - Drori, R.; Li, C.; Hu, C.; Raiteri, P.; Rohl, Andrew; Ward, M.; Kahr, B. (American Chemical Society, 2016)
Safranine O, a synthetic dye, was found to inhibit growth of ice at millimolar concentrations with an activity comparable to that of highly evolved antifreeze glycoproteins. Safranine inhibits growth of ice crystals along the crystallographic a-axis, resulting in bipyramidal needles extended along the <0001> directions as well as and plane-specific thermal hysteresis (TH) activity. The interaction of safranine with ice is reversible, distinct from the previously reported behavior of antifreeze proteins. Spectroscopy and molecular dynamics indicate that safranine forms aggregates in aqueous solution at micromolar concentrations. Metadynamics simulations and aggregation theory suggested that as many as 30 safranine molecules were preorganized in stacks at the concentrations where ice growth inhibition was observed. The simulations and single-crystal X-ray structure of safranine revealed regularly spaced amino and methyl substituents in the aggregates, akin to the ice-binding site of antifreeze proteins. Collectively, these observations suggest an unusual link between supramolecular assemblies of small molecules and functional proteins.